Some Somatometric Indicators of Pregnant Women Living in Rural Conditions - Boymuratovna, Buranova Gulnoza; Shokirovich, Rakhmatullayev Yorqin (American Journal of Biology and Natural Sciences, 2025)
This study examines somatometric parameters in pregnant women aged 18-29 and 30-39. The findings indicate that while the subjects’ Ketle index remains within normative values, their weight gain demonstrates a significant increase in the second and third trimesters compared to the first. This pattern of gestational weight gain is likely influenced by a combination of maternal age, environmental conditions, and obstetric history, including parity.